Elevated lung volumes in neonates with bronchopulmonary dysplasia measured via MRI. Issue 8 (27th May 2019) - Yoder, Lauren M.; Higano, Nara S.; Schapiro, Andrew H.; Fleck, Robert J.; Hysinger, Erik B.; Bates, Alister J.; Kingma, Paul S.; Merhar, Stephanie L.; Fain, Sean B.; Woods, Jason C.
Abstract: Background: Bronchopulmonary dysplasia (BPD) is a chronic lung disease of prematurity defined by requirement for respiratory support at 36 weeks postmenstrual age (PMA), but structural sequelae like lung hyperinflation are often not quantified. Quiet‐breathing, nonsedated magnetic resonance imaging (MRI) allows tomographic quantification of lung volumes and densities. We hypothesized that functional residual capacity (FRC) and intrapleural volume (IV) are increased in BPD and correlate with qualitative radiological scoring of hyperinflation. Methods: Ultrashort echo time (UTE) MRI of 17 neonates (acquired at ~39 weeks PMA) were reconstructed at end‐expiration and end‐inspiration via the time course of the k0 point in k‐space. Images were segmented to determine total lung, tidal, parenchymal tissue, and vascular tissue volumes. FRC was calculated by subtracting parenchymal and vascular tissue volumes from IV. Respiratory rate (RR) was calculated via the UTE respiratory waveform, yielding estimates of minute ventilation when combined with tidal volumes (TVs). Two radiologists scored hyperinflation on the MR images. Results: IV at FRC increased in BPD: for control, mild, and severe (patients the median volumes were 32.8, 33.5, and 50.9 mL/kg, respectively. TV (medians: 2.21, 3.64, and 4.84 mL/kg) and minute ventilation (medians: 493, 750, and 991 mL/min) increased with increasing severity of BPD (despite decreasing RR, medians: 75.6, 63.0, and 56.1 breaths/min). FRC increased with increasing severity of BPD (39.3, 38.3, and 56.0 mL, respectively). Findings were consistent with increased hyperinflation scored by radiologists. Conclusions: This study demonstrates that UTE MRI can quantify hyperinflation in neonatal BPD and that lung volumes significantly increase with disease severity.